Public Library Use of Geographic Information Systems in the United States. Issue 8 (17th November 2018) - Arendt, Anne; Morris, Anthony; Stephens, Mary
Abstract: Public libraries are a source of information and resources for the local community, they also play a role in the use of technologies such as geographic information systems (GIS) in that regard. GIS uses maps as output mediums for displaying demographic or similar information, as well as for spatial comparison or spatially based analysis. This is useful for gaining knowledge as well as for decision making. This article reports research into the awareness and use of GIS-type systems in public library settings in hopes of better understanding the benefits, drawbacks, and limitations to use of systems such as these. Primary findings suggest that there continues to exist limited understanding of the capabilities of GIS technology in public libraries and therefore very little demand for it exists in public librarians and patrons alike.